2019
DOI: 10.3389/fnins.2019.00855
|View full text |Cite
|
Sign up to set email alerts
|

A Swarm Optimization Solver Based on Ferroelectric Spiking Neural Networks

Abstract: As computational models inspired by the biological neural system, spiking neural networks (SNN) continue to demonstrate great potential in the landscape of artificial intelligence, particularly in tasks such as recognition, inference, and learning. While SNN focuses on achieving high-level intelligence of individual creatures, Swarm Intelligence (SI) is another type of bio-inspired models that mimic the collective intelligence of biological swarms, i.e., bird flocks, fish school and ant colonies. SI algorithms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 56 publications
(80 reference statements)
0
14
0
Order By: Relevance
“…While PCM and ReRAM technologies have been widely used in neuromorphic systems in the past years [78], ferroelectric technology has only recently been investigated for these applications [15]. The systems reported are mainly at simulation level, for both FTJs [34,35,37] and FeFETs [57,[79][80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…While PCM and ReRAM technologies have been widely used in neuromorphic systems in the past years [78], ferroelectric technology has only recently been investigated for these applications [15]. The systems reported are mainly at simulation level, for both FTJs [34,35,37] and FeFETs [57,[79][80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fang et al demonstrated that certain optimization problems could be solved driven by the coupled dynamics of ferroelectric ïŹeld‐effect transistor (FeFET)‐based spiking neurons. [ 84 ] While there was no synaptic weight adaptation in this approach, the optimal solution to the problem is determined by the coupled interactions between the neurons, which modulate each other's membrane potentials in an event‐driven manner.…”
Section: Snns and Memristorsmentioning
confidence: 99%
“…Especially, Spiking Neural Networks (SNNs) process binary spikes through time like a human brain, resulting in 1-2 order of magnitude energy efficiency over ANNs on emerging neuromorphic hardware [42,11,1,4]. Due to the energy advantages and neuroscientific interest, SNNs have made great strides on various applications such as image recognition [31,26,6], visualization [27], optimization [8,9], and object detection [24]. Therefore, SNNs have a huge potential to be exploited on real-world edge devices.…”
Section: Introductionmentioning
confidence: 99%